Effects of herpesviral US3 protein kinase on DNA damage - Miettinen, Laura (2023)
Herpes simplex virus type 1 is an enveloped human pathogen that can be engineered for oncolytic virus therapy. The viral genome encodes the US3 protein kinase which regulates many cellular and viral processes during infection. For example, US3 protein kinase is a known inhibitor of caspase-3 activation. Caspase-3 activates caspase-activated DNAse, which fragments DNA during apoptosis. The connection between US3 and DNA fragmentation has yet to be demonstrated. This thesis investigates the effect of viral US3 protein kinase on cellular DNA damage. In these studies, we compared the amount of DNA damage in cells infected with herpes simplex type 1 US3 deletion virus and the repair virus with reinserted US3 gene. Cell viability and the amount of DNA damage and nuclear caspase-activated DNAse during infections were analyzed with the comet assay, trypan blue staining, and confocal microscopy. We found that infected cells with US3 deletion virus had increased DNA damage 12 hours post infection and had higher fluorescence intensity in DNA damage loci at 16 hours post infection compared to US3 repair virus infected cells. Based on the comet assay, it was found that herpes infection caused DNA damage in the host genome regardless of whether it contained the US3 protein. The intensity of caspase-activated DNAse in the nucleus was decreased in the US3 deletion virus infection compared to repair virus infection at eight and twelve hours post infection. The viability of US3 deletion virus infected cells decreased significantly between twelve and sixteen hours post infection. As a conclusion, DNA damage was more extensive in US3 deletion virus infected cells than in US3 repair virus infected cells. In conclusion, our results suggest that US3 protects the host cell genome from DNA damage during herpes infection. However, the higher amount of the DNA damage in US3 deletion virus infection could not be attributed to an increased presence of caspase-activated DNAse in the nucleus. It is highly likely that the US3 protein may phosphorylate yet unknown cellular and viral proteins, and these phosphorylation events potentially affect the amount of DNA damage in the infected cell.